UiTM and Cardiff Metropolitan University have won the UK-Malaysia Education Institutional Partnership of the Year - UiTM, Pejabat Timbalan Naib Canselor (Penyelidikan & Inovasi) (UiTM, 2024)
News and activities Office of Deputy Vice-Chancellor (Research & Innovation) Feb 2024.